STUDENT PERCEPTION USING DUET CONTENT ON TIKTOK APPLICATION TO ENHANCE SPEAKING SKILLS IN INDONESIAN VOCATIONAL SCHOOL STUDENTS - Ngelbanip Fydi Tapyor; Saiful Anwar (Esteem Journal of English Education Study Programme, 2025)
TikTok stands out from other social media platforms due to its advanced algorithm, which analyzes user behaviors like search history, likes, and watch time to provide personalized video recommendations on its For You Page (FYP). Unlike other platforms, which require users to search for content using specific keywords, TikTok uses sophisticated artificial intelligence to tailor content, contributing to its popularity, especially among users aged 14 to 30, including students. The platform's short videos and hashtag-driven content, such as #duetme, have become popular, enabling collaborative English conversations. This study investigates the views of vocational high school students at SMK Sritanjung Banyuwangi on using TikTok's duet feature to improve their creative English-speaking skills. Using a qualitative research design, data were gathered through questionnaires and interviews. The results show that 11 out of 18 students reported a boost in their confidence when creating English conversation duets on TikTok, indicating the platform's potential as an effective tool for enhancing English communication.